Tin(IV) Complexes of Bidentate Schiff Bases Having NS Donor Systems - Raizada, M.R. (Asian Journal of Chemistry, 2010)
Nine new tin(IV) complexes of bidentate thiosemicarbazate Schiff bases have been synthesised. The mode of bonding of the ligands is via azomethine nitrogen and thiolo sulphur atom as revealed by IR and PMR data. These complexes were screened for antibacterial activity.